Assessment of two new molecular based methods for identification of Candida parapsilosis sensu lato species - Garcia, Guillermo Manuel (2011)
Candida parapsilosis sensu stricto, C. orthopsilosis, and C. metapsilosis replaced C. parapsilosis groups I, II, and III in 2005. Since then, an increased interest in studying their epidemiology has arisen based on the observed differences in antifungal susceptibilities and virulence the three species. A strict differentiation of these species cannot be achieved by phenotypic methods. We evaluate two new molecular methodologies to differentiate among these species by the use of a collection of 293 bloodstream infection isolates of C. parapsilosis sensu lato. For the first method, the isolates were studied using PCR amplification of a fragment of the C. parapsilosis sensu lato FKS1 gene and a universal primer pair followed by EcoRI enzyme digestion. The other method used the allele discrimination ability of molecular beacons in a multiplex real-time PCR format. Both methods of identification showed 100% concordance with internal transcribed spacer 1 (ITS1)/ITS2 sequencing and proved to be effective for clinical applications, even with mixed-species DNAs.